Adaptive evolution of Gluconobacter oxydans accelerates the conversion rate of non-glucose sugars derived from lignocellulose biomass. (October 2019) - Jin, Ci; Hou, Weiliang; Yao, Ruimiao; Zhou, Pingping; Zhang, Hongsen; Bao, Jie
Highlights: An adaptive evolution of G. oxydans by alternate culture strategy was carried out. Conversion rate of non-glucose sugars was improved by several folds. All lignocellulose-derived sugars were converted into alcohols and acids. Significant up-regulation of mGDH gene was found in adapted G. oxydans. Abstract: Gluconobacter oxydans is capable of oxidizing various lignocellulose derived sugars into the corresponding sugar acids including glucose, xylose, arabinose, galactose and mannose, but simultaneous utilization of these sugars is difficult. This study attempted an adaptive evolution of G. oxydans by alternate transfer in inhibitors containing hydrolysate and inhibitors free hydrolysate for intensifying sugars simultaneous utilization. After 420 days' continuous culture, the conversion rate of all non-glucose sugars significantly improved by several folds and achieved complete conversion of lignocellulose-derived sugars to the corresponding sugar acids. The significant up-regulation of mGDH gene in the adapted G. oxydans strain (more than 40-fold greater than the parental) was considered as the decisive factor for the improvement of strain performance. This evolution adaptation strategy also could be used to accelerate robust sugars utilization for other fermented strains in lignocellulose biorefinery.